Prognostic value of early treatment response to craniospinal irradiation in diffuse leptomeningeal glioneuronal tumors: a case series - Balcı Topuz, Beril; Bozkurt Vardar, Tuğçe; Öztürk İyilikci, Meltem; Eraslan, Cenk; Ataseven, Eda; Bolat, Elif; Ertan, Yeşim; Akalın, Taner; Kamer, Serra (The Turkish Journal of Pediatrics, 2025)
Background. Diffuse leptomeningeal glioneuronal tumors (DLGNTs) are rare pediatric central nervous system neoplasms with poorly defined treatment strategies and prognostic factors. Although chemotherapy (CHT) is frequently used, the role of radiotherapy (RT), particularly craniospinal irradiation (CSI), remains unclear.Case Presentations. We present a case series of three pediatric patients diagnosed with DLGNTs and treated with CSI at an initial dose of 36 Gy, with an additional boost to 54 Gy. Patients were evaluated for early radiological response post-CSI and its potential prognostic implications, alongside their clinical and histological features. Two patients demonstrated significant radiological regression after 36 Gy of CSI, with continued improvement 1.5 months post-treatment. These patients remained stable for 88 and 27 months, respectively, without further disease progression. The third patient exhibited disease progression despite CSI and concurrent temozolomide, ultimately succumbing to the disease within 10 months. Notably, this patient had a Ki-67/MIB-1 index of 70%, while surviving patients had lower proliferation indices.Conclusions. Our findings suggest that an early favorable response to 36 Gy of CSI may serve as a prognostic indicator in DLGNTs. This study highlights the potential value of CSI in managing these tumors and underscores the need for further research to establish standardized treatment approaches.
Keywords: craniospinal irradiation; diffuse leptomeningeal glioneuronal tumor; pediatrics; central nervous system neoplasms; prognosis